Product awareness and behavioural intention to use of customizable mobile data plan: case study of Yoodo – Celcom / Amirah Amin, Danial Zarkasyi Mazlan and Fatin Farhana Mohd Suhaimi - Amin, Amirah; Mazlan, Danial Zarkasyi; Mohd Suhaimi, Fatin Farhana (2019)
The purpose of this study was to determine the level of product awareness of Yoodo by Celcom and behavioural intention to use of customizable mobile data plan. The study examined the relationship between performance expectancy, effort expectancy, perceived risk and price value with behavioural intention to use of customizable mobile data plan. The study used 300 samples size with the range of age above 18 years old living in Klang Valley region. Result of the study showed that the level of awareness for Yoodo product was low as only 31% from the respondents have heard about Yoodo and the rest which is 69% of them claimed they never heard of Yoodo before. From the study, result also showed that there were significant relationships between performance expectancy, perceived risk and price value with behavioural intention to use of customizable mobile data plan. As for effort expectancy, there is no significant relationship between effort expectancy and behavioural intention to use of customizable mobile data plan. In conclusion, Celcom needs to improve their marketing strategy in promoting Yoodo to the public as the level of product awareness is still low. Apart from that, Celcom needs to be more aggressive in portraying that Yoodo is one of its products as it will increase the number of customers. This has been proven in one of the result where more than half of respondents (53.7%) claimed that they will be more interested to subscribe to Yoodo as their mobile plan knowing that Yoodo is under Celcom.